Origin of Serum Affects Quality of Engineered Tissues Produced by the Self-Assembly Approach. (16th May 2016) - Chabaud, Stéphane; Simard, Melissa; Gendreau, Isabelle; Pouliot, Roxane; Bolduc, Stéphane
Abstract : Despite the emergence of serum-free media for cell culture, the use of serum to supplement the culture media is still essential in order to produce engineered urologic tissues using the self-assembly approach, not only for the stromal compartment but also for the uroepithelium. Effects of sera on thickness of these two compartments were measured and quality of the epithelial differentiation was evaluated. For bladder mucosa substitute reconstruction, the use of postnatal sera failed to produce an adequate uroepithelium whereas the fetal sera supplementation did. Postnatal sera also provided thinner stromal compartments than the one obtained using fetal sera, no matter if the fibroblasts from healthy or psoriatic donors were used to reconstruct human skin substitutes.